2013
DOI: 10.2106/jbjs.l.00356
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tunnel Widening with Autogenous Bone Plugs Versus Bioabsorbable Interference Screws for Secondary Fixation in ACL Reconstruction

Abstract: The clinical results associated with bioabsorbable screws and bone plugs were not significantly different. Laxity evaluation demonstrated no significant differences between bioabsorbable screws and bone plugs. Compared with bioabsorbable interference screws, autogenous bone plugs reduced the complication rate and tibial tunnel widening without inducing instability. We believe that an autogenous bone plug for the tibial tunnel is a reasonable option in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…The widest tunnel diameter was noted at different levels in relation to the joint 3,9,10,17,18,20,22,38,44 . The percentages of the absolute values to the original drill bit size were calculated 3,9,10,17,18,20,22,38,44 . Susceptibility artifacts, caused by metallic implants such as buttons, screws or pins, which are commonly used in ACL surgery, can limit 17 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The widest tunnel diameter was noted at different levels in relation to the joint 3,9,10,17,18,20,22,38,44 . The percentages of the absolute values to the original drill bit size were calculated 3,9,10,17,18,20,22,38,44 . Susceptibility artifacts, caused by metallic implants such as buttons, screws or pins, which are commonly used in ACL surgery, can limit 17 .…”
Section: Discussionmentioning
confidence: 94%
“…The percentages of the absolute values to the original drill bit size were calculated 1, 7, 8, 15, 26, 31-33, 37, 39, 41-43, 46, 47 . In contrast to CT, MRI promises not only structural information on the tunnels, but also allows evaluation of the ACL graft itself 3,9,10,17,18,20,22,38,44 . Major drawback is the limited assessment of osseous structures in MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the tibial side, the previous studies used the bone plug to reduce TW 1718. To obtain a strong bone-to-bone healing on the tibial side, we also recommended a bone plug.…”
Section: Methodsmentioning
confidence: 99%
“…The biological factors proposed include an antigenic immune response,11 a toxic effect,1 a nonspecific inflammatory response,12 and cellular necrosis from drilling and graft remodeling,131415 and the mechanical factors proposed include local stress deprivation of the tunnel wall,15 graft-tunnel motion,12 aggressive rehabilitation,16 and increased graft forces due to improper graft placement. Many recent studies have tried to prevent TW by modifying the surgical techniques used; strategies include the use of a bone plug application with press-fit,1718 bone impaction using a dilator,19 proper tunnel positioning,8 and a periosteal envelope 5. It has been reported that these surgical procedures can effectively reduce the extent of TW; however, there is still controversy regarding the most effective method of preventing TW.…”
Section: Introductionmentioning
confidence: 99%